Validitas Modul Ajar Pada Materi Adab Bersosial Media dalam Pandangan Islam di Kelas 8 MTS Terpadu Berkah - Rabbiatul Alawiyah; Reza Maulana Dalimunthe; Hadma Yuliani (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
The rapid development of digital technology demands character education as well as ethical guidelines for interacting in social media, especially social media manners in Islamic views at Berkah Integrated MTs Palangkaraya. This study aims to assess the validity of teaching modules on adab social media in the view of Islam for class VIII students of MTs Terpadu Berkah. The research method used is Research and Development (R&D) with the ADDIE model at the analysis and design stages. Validation was carried out by four experts, namely 2 material experts, and 2 design experts. The assessment included six aspects: content suitability, alignment with the curriculum, relevance to students, language, layout and design, and learning evaluation. Data were analyzed using a Likert scale to calculate the percentage of validity. The results showed that the teaching module had an average validity of 80%, which included the valid category. This shows that the module is feasible to use in learning. However, there are some minor revisions that need to be made, such as improving visual design, images, fonts, and simplifying language, and adding learning activities that are more interactive and fun. In conclusion, this teaching module can be used as a teacher's guide in learning that helps students understand and apply social media manners in accordance with Islamic values. Additional revisions from validators are expected to increase the effectiveness of the teaching module for students